2012
DOI: 10.1080/0376835x.2012.645645
|View full text |Cite
|
Sign up to set email alerts
|

Gendered trends in poverty in the post-apartheid period, 1997–2006

Abstract: This study investigates whether trends in the extent, depth and severity of poverty in South Africa over the past decade have been gendered. We examine first whether females are more likely to live in poor households than males, and whether this has changed over time; and, second, how poverty has changed among female-headed and male-headed households. We use data provided by the 1997 and 1999 rounds of the October Household Survey and the 2004 and 2006 rounds of the General Household Survey. These surveys have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 22 publications
5
53
0
Order By: Relevance
“…This study has demonstrated that the size, composition and economic profile of the middle class in South Africa are very different across these two broad definitions. Given extensive poverty and income inequality in South Africa (Hoogeveen & Ö zler, 2006;Leibbrandt et al, 2010;Posel & Rogan, 2012), individuals living in households which are 'middle of the road' in the national income distribution do not possess the socio-economic status typically associated with middleclass affluence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has demonstrated that the size, composition and economic profile of the middle class in South Africa are very different across these two broad definitions. Given extensive poverty and income inequality in South Africa (Hoogeveen & Ö zler, 2006;Leibbrandt et al, 2010;Posel & Rogan, 2012), individuals living in households which are 'middle of the road' in the national income distribution do not possess the socio-economic status typically associated with middleclass affluence.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 indicates that the 'middle tercile' definition has the widest income boundary for the middle class, with 4.56 million households falling within this income threshold. This includes some 1.19 million households that fall below a commonly adopted poverty line of R515 per capita per month in 2008 prices (see Hoogeveen & Ö zler, 2006;Leibbrandt et al, 2010;Posel & Rogan, 2012). The '50 to 150% median' definition uses a narrower range of income to identify households as middle class and also selects households which are generally poorer.…”
Section: The Middle Income Strata: a Relative Approachmentioning
confidence: 99%
“…Poverty remains at the core of South Africa's developmental challenges, even though the country has been largely successful in reducing poverty, both in monetary terms and in multidimensional forms of deprivation (Posel & Rogan, 2012). Many measurement approaches consider poverty as a shortfall in resources, whether in income, consumption expenditures or a lack of essential goods.…”
Section: Motivationmentioning
confidence: 99%
“…Recent findings paint a dismal picture: there is a significant gender difference in unemployment (Okojie, 2003); the Gini coefficient is 0.58, making South Africa one of the most unequal countries in the world (Demombynes & Ö zler, 2005:267); approximately 57% of the population live below the poverty income line of US$2 per day (Agüero et al, 2007); labour force participation is gender-skewed, with the average rate being 34.2% for women and 52.1% for men; and the feminisation of poverty is becoming increasingly apparent (Shisana et al, 2010). According to Leibbrandt et al (2010) and Posel & Rogan (2012), poverty estimates are significantly and consistently higher for women (especially African women) than for men. The unemployment rate, 25.5% at the time of writing (Stats SA, 2011), is one of the highest in the world.…”
Section: Introductionmentioning
confidence: 99%